Increased expression of cystathionine beta-synthase and chemokine ligand 21 is closely associated with poor prognosis in extrahepatic cholangiocarcinoma. Issue 38 (18th September 2020) - Wang, Lingxiang; Yang, Zhulin; Wu, Zhengchun; He, Jun; Xu, Shu; Li, Daiqiang; Zou, Qiong; Yuan, Yuan
Abstract : Abstract: The expression of Cystathionine beta-synthase (CBS) and Chemokine ligand 21 (CCL21) is associated with the tumorigenesis and progression of a variety of tumors, but whether alterations in their expression levels correlates with the carcinogenesis and progression of EHCC is still unknown. This study investigated the clinicopathological significance of CBS and CCL21 expression in EHCC. We investigated the correlations between the expression of CBS and CCL21 and clinicopathological characteristics in EHCC using EnVision immunohistochemistry. The expression of CBS and CCL21 was significantly higher in EHCC tumors than in nontumor tissues ( P < .05 and P < .01). EHCC patients with CBS and CCL21 expression combined with lymph node metastasis, tumor cell invasion, and TNM III/IV stage had more severe conditions than those with no lymph node metastasis, distant invasion and TNM I/II stage ( P < .01). Kaplan-Meier survival analysis showed that the overall survival rates for EHCC patients with negative CBS or CCL21 reaction were significantly higher than those for patients with positive CBS or CCL21 reaction(( P < .01). CBS or CCL21 expression was revealed as an independent poor prognostic factor for EHCC patients by Cox multivariate analysis. The present study indicates that CBS and CCL21 expression is closely associated with the pathogenesis of clinical, pathological and biological behaviors and poor prognosis in EHCC.